THEORETICAL FOUNDATIONS FOR THE STUDY OF LANGUAGE NOMINATION - Toyloqov Oybek Panjiyevich (Scholar Express Journal, 2023)
This article is written about theoretical foundations for the study of language nomination, the problem of studying language nomination in linguistics and language nominations of football teams, players and their non-verbal actions
Keywords: language; denomination; theory; linguistics